TEACHER"™S STRATEGY IN PREVENTING ACTS OF VIOLENCE THROUGH THE CHILD-FRIENDLY SCHOOL PROGRAM - Fitriyani, Nur Liya; Wulan, Tyas Retno; Mintarti, Mintarti (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
Although regulations regarding child-friendly school policies have been made by the government since 2014. However, the reality is that we often find cases of violence against children in educational institutions covered by social media. Cases of violence that often occur in educational institutions include physical violence, sexual violence, and psychological violence. In this study, researchers were very interested and wanted to research teacher strategies for preventing acts of violence through child-friendly school programs. This aims to map teacher strategies from the results of research on child-friendly schools that have been conducted by several previous researchers. This study uses a qualitative approach with the method of a literature review or literature study. It is hoped that the results of this strategy mapping can be put to good use in the future by educational institutions in Indonesia to implement a child-friendly school program. The results of the study show that educational institutions that have implemented a child-friendly school program have tried to follow the rules by the six standard indicators set by the government. Teachers are required to carry out fun learning, invite students to actively participate, also provide more educational punishments if students make mistakes. Several educational institutions are also innovating by creating literacy activities, clean Fridays, strengthening character education, creating educational content for children through social media, and providing counseling services that students and parents can access.